2013
DOI: 10.1161/hyp.62.suppl_1.a59
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 59: Targeted Angiotensin Converting Enzyme Overexpression in Myelomonocytic Cells Prevents Cognitive Decline in Alzheimer’s Disease

Abstract: The cognitive decline in Alzheimer's disease (AD) is associated with elevated brain levels of amyloid β-protein (Aβ), particularly Aβ 1-42 . Angiotensin-converting enzyme (ACE) can enzymatically degrade Aβ 1-42 and its overexpression in myelomonocytic cells enhances their immune function. To examine the effect of targeted ACE overexpression on AD, we crossed ACE 10/10 mice, which over express ACE in myelomonocytic cells, with the double-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…By contrast, ACE 10/10 mice that express ACE in peripheral myelomonocytes (and microglia -Fig. S1) have reduced Aβ deposition, neurodegeneration and improved learning and memory deficits when crossed to the APP/PS1 Aβ producing mice (31). Here, we found that selective expression of ACE in microglia/CAMs potentiates their ability to process Aβ.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…By contrast, ACE 10/10 mice that express ACE in peripheral myelomonocytes (and microglia -Fig. S1) have reduced Aβ deposition, neurodegeneration and improved learning and memory deficits when crossed to the APP/PS1 Aβ producing mice (31). Here, we found that selective expression of ACE in microglia/CAMs potentiates their ability to process Aβ.…”
Section: Discussionmentioning
confidence: 60%
“…Overexpression of ACE in myelomonocytes which included microglia in the APP/PS1 amyloid mouse model, decreased amyloid plaque formation and improved learning and memory that were dependent on ACE catalytic activity, but independent of blood pressure regulation (31).…”
Section: Introductionmentioning
confidence: 97%
“…This enhancement ultimately reduces the formation of atherosclerotic plaques in adenoassociated virus-proprotein convertase subtilisin/kexin type 9 (AAV-PCSK9)-induced atherosclerosis in ACE10/10 mice (7,8). We further showed that ACE 10/10 macrophages stimulate abundant ATP production dependent on Kreb's cycle intermediates compared with WT cells (9)(10)(11)(12). Hence, our findings suggest that the upregulation of ACE may positively enhance metabolic reactions in macrophages, which ultimately provides a protective effect in atherosclerosis.…”
Section: Introductionmentioning
confidence: 57%
“…For instance, the immunopathogenesis of Alzheimer's disease (AD) contains failing lipid handling and metabolism of brain microglia which possess similar differentiation origin and functional character with peripheral macrophage. In fact, we have already found that ACE10/10 mice showed highly resistant character in the AD model (9,10). We revealed that ACE10/10 microglia captured and degraded amyloid beta (Ab) as one of the potential benefits to attenuate AD symptom; however, there is a possibility that lipid metabolism is enhanced by ACE overexpression in the microglia.…”
Section: Discussionmentioning
confidence: 99%